Timeless or Timely? Vantage Points of Mosque Design (American Journal of Islam and Society, 2017)
Books Reviewed:Azra Akšamija, Mosque Manifesto: Propositions for Spacesof Coexistence. Berlin: Revolver Publishers, 2015; Christiane Gruber, ed., IslamicArchitecture on the Move: Motion and Modernity. Bristol: Intellect, 2016;Bernard O’Kane, The Mosques of Egypt. Cairo: American University in CairoPress, 2016.It may seem to some people that writing about the architecture of Islam andthe mosque, the Islamic building par excellence, is an exercise in reiteratingthe past and earlier finds – possibly packaging what is already known in anattractive visual format. What these three books have in common is the effortto analyze these two subjects in a new way and in line with three very differentmethods. Azra Akšamija’s Mosque Manifesto: Propositions for Spacesof Coexistence is a collection of ten of her original research-creation piecesframed by ten articles. Research-creation is a hybrid scholarly approach that“supports the development of knowledge and innovation through artistic expression,scholarly investigation, and experimentation.”1Although she doesnot use this term, one should keep it in mind while reviewing the context andimpact of her artistic work. Trained as an architect, she is also a historian andpracticing artist, a designer and professor. Her productions critically reviewand express her proposed ten points of design. This vantage point is clearlyunique, in that the material is primary and generative.Christiane Gruber’s edited Islamic Architecture on the Move: Motion andModernity compiles the voices of eight academics reflecting on specific aspectsof the physical and ideological movement of Islamic ideas and forms. Someof the contributions rely heavily on previous research; however, three essaysare original research. In The Mosques of Egypt, O’Kane showcases his photographsof over eighty mosques. His academic expertise and experience in editingthe works of renowned Islamic scholars gives him a unique position, andhis excellent book includes both contemporary and detailed documentation ofwell-studied buildings, several lesser known structures, and several modernmosques.Tellingly, each book’s structure betrays a great deal about how its contentis to be received, for those who practice and study the arts are well aware ofan object’s power of visual and tactile qualities, even if that object happens to ...